Proceso de Atención de Enfermería en Paciente de 58 años con Tuberculosis Pulmonar. - Vera Jama, Romina Adriana (2022)
Worldwide, tuberculosis has been highlighted as one of the highest risk diseases, it affects the lungs in an infectious way and is caused by a bacterium known as (Mycobacterium tuberculosis). Nursing has stood out in health worldwide due to its high demand for attention and care under established protocols towards patients, whether within hospitals, health centers or providing services in particular. In this clinical case we will talk about a 58-year-old female patient, with a medical diagnosis of Pulmonary Tuberculosis. The patient is referred to the Enrique Ponce Luque health center in the city of Babahoyo, where she underwent different studies, in which she obtained a positive PCR result for tuberculosis, she is immediately attended by the personnel in charge of the program. Family Physician provides the consultation, performs the cephalocaudal examination where we obtain a low body mass index, for which he proceeds to refer consultation with nutrition to provide a balanced diet. The patient is visited at home by members of the health personnel where she is given education about her pathology, it is explained to her that in order to take her medications she must go to the operating unit, constant controls and home visits will be carried out to analyze whether the expected result of his disease is being given and thus determine new protocols in his treatment. Nursing will apply the nursing care process, to obtain a good diagnosis, interventions and results, it will also be guided by the functional patterns of Marjory Gordon, the Virginia Henderson model based on the 14 basic needs and the Dorothea Orem model based on the 14 basic needs. in self-care.